Banxia-Yiyiren alleviates insomnia and anxiety by regulating the gut microbiota and metabolites of PCPA-induced insomnia model rats - Wang, Liang; Qi, Xiaorong; Wang, Shuo; Tian, Chujiao; Zou, Tao; Liu, Zihan; Chen, Qi; Chen, Yingfan; Zhao, Yunshan; Li, Shaodan; Yang, Minghui; Chai, Ningli (Frontiers in Microbiology, 2024)
Objective: The objective of this study was to clearly define effects of Banxia-Yiyiren on the gut microbiota and its metabolites in PCPA-induced insomnia model and the possible underlying mechanisms involved.Materials and methods: 16S rRNA gene sequencing combined with metabonomic analysis was used to explore the mutual effects of the PCPA-induced insomnia model and the gut microbiota and the intrinsic regulatory mechanism of Banxia-Yiyiren on the gut microbiota and metabolites in the PCPA-induced insomnia model.Results: Banxia-Yiyiren was identified by mass spectrometry to include amino acids, small peptides, nucleotides, organic acids, flavonoids, fatty acids, lipids, and other main compound components. The EPM test results revealed that high-dose Banxia-Yiyiren may increase willingness to explore by improving anxiety-like symptoms caused by insomnia. Through 16S rRNA gene sequencing, at the phylum level, compared with those in G1, the relative abundances of Bacteroidota and Proteobacteria in G2 increased, whereas the relative abundance of Firmicutes decreased. At the genus level, compared with those in G1, the relative abundances of Prevotella_9, Prevotella, Ralstonia, Escherichia-Shigella, and UCG-005 in G2 increased, whereas the relative abundances of Lactobacillus, Ligilactobacillus, Alloprevotella, Blautia, and Prevotellaceae_NK3B31_group decreased. The results of the metabolomics analysis revealed 1574 metabolites, 36.48% of which were classified as lipids and lipid-like molecules, 20.76% as organic acids and their derivatives, and 13.36% as organic heterocyclic compounds. The correlation between the top 20 differentially abundant metabolites in the G1–G2 groups was greater than that between the G3–G2 and G6–G2 groups. KEGG enrichment analysis revealed that the main differentially abundant metabolites in each group were significantly enriched in various pathways, such as amino acid metabolism, ABC transporters, protein digestion and absorption. Additionally, there was a significant Pearson correlation between the genus-level differences in gut microbiota and the differentially abundant metabolites among the G1-G2, G3-G2, and G6-G2 groups.This study preliminarily verified that PCPA-induced insomnia model is closely related to gut microbial metabolism and microecological disorders, and for the first time, we confirmed that Banxia-Yiyiren can act on the gut microbiota of PCPA-induced insomnia model rats and alleviate insomnia and anxiety by regulating the species, structure, abundance, and metabolites of gut microbiota.